YSO jet simulations: from theory to synthetic observations - Tsinganos, K.; Matsakos, T.; Tesileanu, O.; Vlahakis, N.; Massaglia, S.; Mignone, A.; Trussoni, E.; Cayatte, V.; Stehle, Ch. (2013)
A plethora of analytical studies have addressed the physical mechanisms of jet launching and propagation in young stellar objects. However, their link to observations is still missing due to the complexity of the emission processes involved. In this work we address this issue, by presenting MHD simulations of two-component YSO jet models that are based on analytical disk and stellar outflow solutions. We include ionization and optically thin radiation losses during the temporal evolution of the flow and we post process the output files to generate synthetic emission maps. Our results are confronted to observational data and we find that our models predict the correct range of values for the density, temperature and velocity of YSO jets. Moreover, the synthetic emission maps of the - 39 - doublets [OI], [N II] and [S II] outline a well collimated and knot-structured jet, which is surrounded by a less dense and slower wind, not observable in these lines. The jet is found to have a small opening angle and a radius that is also comparable to observations.